MIDO GDM: an innovative artificial intelligence-based prediction model for the development of gestational diabetes in Mexican women - Héctor Gallardo-Rincón; María Jesús Ríos-Blancas; Janinne Ortega-Montiel; Alejandra Montoya; Luis Alberto Martinez-Juarez; Julieta Lomelín-Gascón; Rodrigo Saucedo-Martínez; Ricardo Mújica-Rosales; Victoria Galicia-Hernández; Linda Morales-Juárez; Lucía Marcela Illescas-Correa; Ixel Lorena Ruiz-Cabrera; et al. (Scientific Reports, 2023)
Abstract Given the barriers to early detection of gestational diabetes mellitus (GDM), this study aimed to develop an artificial intelligence (AI)-based prediction model for GDM in pregnant Mexican women. Data were retrieved from 1709 pregnant women who participated in the multicenter prospective cohort study ‘Cuido mi embarazo’. A machine-learning-driven method was used to select the best predictive variables for GDM risk: age, family history of type 2 diabetes, previous diagnosis of hypertension, pregestational body mass index, gestational week, parity, birth weight of last child, and random capillary glucose. An artificial neural network approach was then used to build the model, which achieved a high level of accuracy (70.3%) and sensitivity (83.3%) for identifying women at high risk of developing GDM. This AI-based model will be applied throughout Mexico to improve the timing and quality of GDM interventions. Given the ease of obtaining the model variables, this model is expected to be clinically strategic, allowing prioritization of preventative treatment and promising a paradigm shift in prevention and primary healthcare during pregnancy. This AI model uses variables that are easily collected to identify pregnant women at risk of developing GDM with a high level of accuracy and precision.